OVERHEAD COSTS IN PUBLIC WELFARE. - Rorem, C. Rufus (The Accounting Review, 1943)
Abstract There has been considerable public criticism of what appeared to be unduly high costs for the administration of public assistance and relief. Administration expenses have generally been contrasted by legislators and the public with the cash payments made directly to public assistance beneficiaries. Grouping and contrasting expenditures for assistance, on the one hand, and administration, on the other, have encouraged the assumption that costs of administration represent merely the cost of distributing the money expended for assistance. Persons familiar with public assistance operations realize that other functions are also performed. They realize further that the cost incurred for investigating cases, which never receive relief, may be more in the interests of the taxpayer than haphazard and inappropriate disbursements to individuals not entitled to benefits under the public assistance program. The standard classification of public assistance costs is a joint recommendation of the American Public Welfare Association and the Social Security Board. Official participation by staff members of the Social Security Board made it possible to incorporate the thinking and recommendations of the experts concerned with national phases of public welfare administration and accounting.